T Lymphocyte-Derived Exosomes Transport MEK1/2 and ERK1/2 and Induce NOX4-Dependent Oxidative Stress in Cardiac Microvascular Endothelial Cells. (28th September 2022) - Rolski, Filip; Czepiel, Marcin; Tkacz, Karolina; Fryt, Katarzyna; Siedlar, Maciej; Kania, Gabriela; Błyszczuk, Przemysław
Abstract : Background . Activation of endothelial cells by inflammatory mediators secreted by CD4 + T lymphocytes plays a key role in the inflammatory response. Exosomes represent a specific class of signaling cues transporting a mixture of proteins, nucleic acids, and other biomolecules. So far, the impact of exosomes shed by T lymphocytes on cardiac endothelial cells remained unknown. Methods and Results . Supernatants of CD4 + T cells activated with anti-CD3/CD28 beads were used to isolate exosomes by differential centrifugation. Activation of CD4 + T cells enhanced exosome production, and these exosomes (CD4-exosomes) induced oxidative stress in cardiac microvascular endothelial cells (cMVECs) without affecting their adhesive properties. Furthermore, CD4-exosome treatment aggravated the generation of mitochondrial reactive oxygen species (ROS), reduced nitric oxide (NO) levels, and enhanced the proliferation of cMVECs. These effects were reversed by adding the antioxidant apocynin. On the molecular level, CD4-exosomes increased NOX2, NOX4, ERK1/2, and MEK1/2 in cMVECs, and ERK1/2 and MEK1/2 proteins were found in CD4-exosomes. Inhibition of either MEK/ERK with U0126 or ERK with FR180204 successfully protected cMVECs from increased ROS levels and reduced NO bioavailability. Treatment with NOX1/4 inhibitor GKT136901 effectively blocked excessive ROS and superoxide production, reversed impaired NO levels, and reversed enhanced cMVEC proliferation triggered by CD4-exosomes. The siRNA-mediated silencing of Nox4 in cMVECs confirmed the key role of NOX4 in CD4-exosome-induced oxidative stress. To address the properties of exosomes under inflammatory conditions, we used the mouse model of CD4 + T cell-dependent experimental autoimmune myocarditis. In contrast to exosomes obtained from control hearts, exosomes obtained from inflamed hearts upregulated NOX2, NOX4, ERK1/2, MEK1/2, increased ROS and superoxide levels, and reduced NO bioavailability in treated cMVECs, and these changes were reversed by apocynin. Conclusion . Our results point to exosomes as a novel class of bioactive factors secreted by CD4 + T cells in immune response and represent potential important triggers of NOX4-dependent endothelial dysfunction. Neutralization of the prooxidative aspect of CD4-exosomes could open perspectives for the development of new therapeutic strategies in inflammatory cardiovascular diseases.